2006
DOI: 10.12968/bjon.2006.15.18.22021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the prevention of venous thromboembolism

Abstract: Patients undergoing major orthopaedic surgery are at high risk of developing venous thromboembolism (VTE). VTE is preventable and venous prophylaxis consensus groups recommend that each patient is assessed for risk of VTE and then stratified into one of the three categories of risk. Rick stratification enables the choice of the most appropriate preventative interventions. This article examines a decision making framework for VTE prevention with particular focus on a validated risk assessment model (RAM) to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Some studies have shown that PE is an important cause of sudden death in hospitalized patients ( 7 , 10 ). In the absence of DVT prevention measures, 40%–70% of patients with fractures develop DVT during the perioperative period ( 11 ). The incidence of DVT in patients with pelvic fracture was 5%–21.09% ( 12 , 13 ), the incidence of DVT in patients with femoral fracture was 6.85%–32% ( 14 , 15 ), and the incidence of DVT in patients with tibial fracture was 2.09%–16.3% ( 14 , 16 ) after the use of low-molecular-weight heparin (LMWH) and other preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that PE is an important cause of sudden death in hospitalized patients ( 7 , 10 ). In the absence of DVT prevention measures, 40%–70% of patients with fractures develop DVT during the perioperative period ( 11 ). The incidence of DVT in patients with pelvic fracture was 5%–21.09% ( 12 , 13 ), the incidence of DVT in patients with femoral fracture was 6.85%–32% ( 14 , 15 ), and the incidence of DVT in patients with tibial fracture was 2.09%–16.3% ( 14 , 16 ) after the use of low-molecular-weight heparin (LMWH) and other preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate nurses have a critical role in promoting patient assessments and maintaining sustainability with the implementation of clinical practice guidelines. Improving nurse and patient adherence to adopting these guidelines can impact on patient health outcomes and contribute significantly to reducing VTE and its associated complications (Autar, ; Cantrell, Ward, & Van Wicklin, ; Collins et al., ; Findlay, Keogh, & Cooper, ; Fleck, Donovan, & Blank, ; Gibbs, Fletcher, Blombery, Collins, & Wheatley, ; Larkin, Mitchell, & Petrie, ; Morrison, ).…”
Section: Introductionmentioning
confidence: 99%